Valuation Model for The Acquisition of PT Prima Globalindo Logistik Tbk (PPGL) Shares by PT Pelayaran Nasional Ekalya Purnamasari Tbk (ELPI) - Raharjo, Bangkit Widhi; Heikal, Jerry (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The aim of this research is to assess the valuation for the acquisition, which is a strategic goal focused on improving performance through product diversification. By acquiring PT Prima Globalindo Logistik Tbk (IDX: PPGL), PT Pelayaran Nasional Ekalya Purnamasari Tbk (IDX: ELPI) intends to broaden its product portfolio by incorporating PPGL’s existing offerings. The study utilizes a quantitative approach, which involves gathering numerical data and analyzing it with statistical methods. The goal is to determine an appropriate transaction structure and price for PT Prima Globalindo Logistik Tbk (IDX: PPGL) in the acquisition by PT Pelayaran Nasional Ekalya Purnamasari Tbk (IDX: ELPI). A successful execution of this corporate action requires careful calculations to improve the performance of the purchasing company and achieve its primary objective. One of the research objectives is to determine the valuation of PT Prima Globalindo Logistik Tbk (IDX: PPGL) as a business. The Free Cash Flow to Firm (FCFF) method is a suitable approach for valuation in a corporate context. This method, along with other financial measures, is used to estimate the cash generated by the company. To forecast the company's financial performance for the next five years (2024-2028), an analysis of PPGL's financial reports from 2021 to 2023 is necessary. Based on this analysis, the book value of PPGL is IDR 341,912 million, or IDR 443 per share, when calculated using the FCFF method. In comparison, the market value of equity as of December 2023 is IDR 102 per share, which is lower than its book value, resulting in a Price-to-Book Value (PBV) ratio of 0.23. Given this market value and the conditions in the logistics industry, it is recommended to proceed with a buy action for the transaction.